Ideal Cardiovascular Health in the Oldest-Old and Centenarians and Its Association With Disability and Health-Related Quality of Life - Liu, Miao; Kou, Fuyin; Yang, Shanshan; Wang, Shengshu; He, Yao; Zhang, Wuping (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to investigate the distribution of ideal cardiovascular health (ICH) indicators among the oldest-old and centenarians and explore their relationships with disability and health-related quality of life of this population. Methods: 1,002 centenarians from China Hainan Centenarian Cohort Study and 798 oldest-old from the China Hainan Oldest-old Cohort study were the target subjects in this analysis. ICH status, disability and health-related quality of life of study subjects were assessed. Fingdings: The median value of ICH indicators among centenarians and the oldest-old is 4 (4-5) and 3 (3-5), respectively. The ICH indicators with the highest percentage of ideal level/status are fasting plasm glucose (FPG) (90.2% of study subjects are at the ideal level), BMI (89.8% of study subjects are at the ideal level), and smoking (89.4% of study subjects are at the ideal status). The disability rates of basic activities of daily living (BADL) and instrumental activities of daily living (IADL) decrease with the increasing number ICH indicators. The EQ VAS and EQ-5D score show an increasing trend along with the increasing number of ICH indicators (p<0.05). After adjusting related covariates, the risk of disability and lower health-related quality of life decreased gradually with the number of ICH metrics increases (p<0.05). Interpretation: The ICH metrics of centenarians and oldest-old were at a relatively good level, and there was a strong and independent inverse relationship between the number of ICH indicators and disability as well as the lower health-related quality of life.